2022
DOI: 10.1007/s44205-022-00003-0
|View full text |Cite
|
Sign up to set email alerts
|

Electron thermodynamics along magnetic nozzle lines in a helicon plasma

Abstract: The electron cooling rate is experimentally investigated along the magnetic lines of a helicon plasma device operating with different magnetic nozzle shapes. Probe measurements in a 2-D region of the plasma plume outline that the polytropic index of electrons has dissimilar values along distinct streamlines ranging from γe≃1.4 to γe>1.8. Accounting for ionization phenomena as an additional degree of freedom allows to predict a polytropic index smaller than the adiabatic limit. It is observed that a reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…The experiment from Kim proposes a hypothesis that the presence of the radial electric field and axial magnetic flux would limit the electron's motion and reduce the degree of freedom of gaseous from 3 to 2, which allows the g = 2 e condition sustained in adiabatic expansion condition [36]. The similar g e values are also observed in Vinci's measurements [37], yet he attributes the unusual g e value to the non-linear effect or anisotropies processes, such as the present of multiple EEPF populations and instabilities. Nevertheless, the research of the g e provides a consolidate scope for engineering the MN.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The experiment from Kim proposes a hypothesis that the presence of the radial electric field and axial magnetic flux would limit the electron's motion and reduce the degree of freedom of gaseous from 3 to 2, which allows the g = 2 e condition sustained in adiabatic expansion condition [36]. The similar g e values are also observed in Vinci's measurements [37], yet he attributes the unusual g e value to the non-linear effect or anisotropies processes, such as the present of multiple EEPF populations and instabilities. Nevertheless, the research of the g e provides a consolidate scope for engineering the MN.…”
Section: Introductionsupporting
confidence: 52%
“…The observation of the g e approaching/greater the adiabatic expansion processes (g = 1.67 e ) has been experimentally determined by Kim [36] and Vinci [37]. The experiment from Kim proposes a hypothesis that the presence of the radial electric field and axial magnetic flux would limit the electron's motion and reduce the degree of freedom of gaseous from 3 to 2, which allows the g = 2 e condition sustained in adiabatic expansion condition [36].…”
Section: Introductionmentioning
confidence: 97%
“…Alternatively, the magnetized electrons can generate azimuthal diamagnetic and Hall currents arising from density and potential gradients, and the momentum conversion due to the interaction between the azimuthal current and the radial magnetic field enhances the axial thrust as identified by analytical [9], numerical [10][11][12], and experimental studies [13]; it has been shown that the diamagnetic effect is a major contributor for the thrust generation [14][15][16][17]. Therefore, the magnetic nozzle is the converter from the electron internal energy into the thrust energy as discussed in terms of electron thermodynamics [18][19][20][21][22][23][24][25][26]. Numerical studies on the helicon thrusters have also been progressed for understanding the thruster physics and improving the performance [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…is met near the rf antenna. Measurements are performed in a helicon-like plasma source, whose main characteristics have been reported in [5,6,24]. The tube constituting the discharge chamber is made in borosilicate glass with φ = 9.4 cm inner diameter and L = 55 cm length.…”
mentioning
confidence: 99%